Evaluation of the Clinical Outcomes of Regenerative Endodontic Procedures Using Autologous Platelet Concentrate: A Systematic Review and Meta-Analysis - Elnaz Mousavi; Navid Nasrabadi; Samira Jamali; Arian Haddadi (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the clinical outcomes of regenerative endodontic procedures using autologous platelet concentrate. Both regeneration and apexification procedures were examined and compared with each other. Material and Methods: The PRISMA 2020 Checklist has been utilized to carry out the systematic review and meta-analysis for the present study. PubMed, Scopus, Web of Science, EBSCO, Embase, and ISI Web of Knowledge have been reviewed for systematic literature until May 2023. A fixed-effect model and a Mantel-Haenszel methodology have been used to measure the risk ratio's 95% confidence interval. Then, Meta-analyses were carried out utilizing Stata/MP version 17. Results: Duplicate studies were eliminated from the first review, 849 studies' abstracts were reviewed, two authors reviewed 103 papers' full texts, and finally, 20 articles were selected. The survival rate in regenerative endodontic procedures between apexification and regenerative endodontic procedures was -0.01 (RR: -0.01, 95% CI: -0.05, 0.02; p=0.35). Conclusion: Throughout the present meta-analysis, regenerative endodontic therapy is an effective intervention with a high survival and success rate in managing immature necrotic permanent teeth.